2012
DOI: 10.1093/aob/mcs218
|View full text |Cite
|
Sign up to set email alerts
|

Thermal thresholds as predictors of seed dormancy release and germination timing: altitude-related risks from climate warming for the wild grapevine Vitis vinifera subsp. sylvestris

Abstract: The thermal thresholds for seed germination identified in this study (T(b) and θ(50)) explained the differences in seed germination detected among populations. Under the two simulated IPCC scenarios, an altitude-related risk from climate warming is identified, with lowland populations being more threatened due to a compromised seed dormancy release and a narrowed seed germination window.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 34 publications
4
73
0
Order By: Relevance
“…First, parameters calculated in a restricted set of experimental treatments give comprehensive estimations of reproduction in complex environments (Hardegree et al, 1999). This allows, for example, an exploration of plant reproduction in climate change scenarios (Orrù et al, 2012). Second, thermal time parameters are comparable in a standard way across seed individuals, populations and species (Trudgill, Squire & Thompson, 2000).…”
Section: (2) Thermal Time and Plant Reproductionmentioning
confidence: 99%
“…First, parameters calculated in a restricted set of experimental treatments give comprehensive estimations of reproduction in complex environments (Hardegree et al, 1999). This allows, for example, an exploration of plant reproduction in climate change scenarios (Orrù et al, 2012). Second, thermal time parameters are comparable in a standard way across seed individuals, populations and species (Trudgill, Squire & Thompson, 2000).…”
Section: (2) Thermal Time and Plant Reproductionmentioning
confidence: 99%
“…Through both intra-and interspecific comparisons of species' responses to ex situ and in situ environments, insights have been gained of the spatial and temporal components of emergence, with apparent universal applicability across habitats and lifeforms (D€ urr et al, 2015;Orr u et al, 2012;Porceddu, Mattana, Pritchard, & Bacchetta, 2013;Pritchard, Steadman, Nash, & Jones, 1999;Steadman & Pritchard, 2004). Recently, thermal time modelling has been applied to a limited number of species to predict and validate germination performance under various climate change scenarios (Fern andez-Pascual et al, 2015;Ordoñez-Salanueva et al, 2015;Orr u et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…() found that dormancy in Beichun grape (a cross‐breed of V. vinifera × V. amurensis ) was consistently released after prolonged stratification at temperature <15°C, while an exposure of the seeds to 25°C induced a secondary dormancy state. In line with previous research (Ellis et al ., ; Wang et al ., ; Orrù et al ., ), our results show that cold stratification (i.e. winter conditions) successfully broke seed dormancy, although to a different extent across different species.…”
Section: Discussionmentioning
confidence: 62%
“…sylvestris (Willd.) Hegi, Orrù et al ., ; and V. amurensis Rupr., Wang et al ., ]. Therefore, little is known whether the current expansion of wild Vitis species is driven by regeneration from seed.…”
Section: Introductionmentioning
confidence: 99%